Human-Centered Platform Engineering for AI-Driven Omnichannel Automation in Enterprise Contact Centers - Vikas Prasad (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Enterprise contact centers sit at the intersection of customer experience, workforce management, and technology transformation. As artificial intelligence becomes a central capability in service delivery, the question is no longer whether to automate but how to do so in ways that keep human judgment at the center of meaningful decisions. This article proposes a human-centered platform engineering framework for AI-driven omnichannel automation in enterprise contact centers, arguing that the most resilient and scalable architectures are those that treat AI as a collaborative teammate rather than a replacement for frontline agents. The framework addresses modular platform abstraction, omnichannel context preservation, cognitive load reduction, workforce attrition, and end-to-end observability. By examining each of these dimensions through the lens of human-AI collaboration, this work demonstrates that embedding human agency into every layer of an AI-enabled platform produces outcomes that outperform automation-first designs across efficiency, workforce well-being, and organizational trust. Attention is also given to the brand and retention implications of this design philosophy, showing that human-centered AI yields durable competitive value beyond any single operational metric. DOI: https://doi.org/10.17762/ijisae.v14i1s.8241